Biomarkers in liver disease - Patel, Vinood B.; Preedy, Victor R. (Biomarkers in disease, 2017)
There are numerous types of liver disease that may be due to toxic agents (such as alcohol or drugs), infectious agents including viruses, congenital conditions and even poor dietary patterns. It has been suggested that there are over 100 different types. As the consequences of liver failure can be devastating it is important that appropriate diagnosis and monitoring is carried out. Much of this characterisation entails the use of biological indicators, i.e biomarkers. Biomarkers in Liver Disease embraces a holistic approach by combining detailed information on different conditions that affect the liver and the use of biomarkers. Biomarkers are described in terms of conventional, new and emerging analytes, techniques, platforms and applications. It covers the latest knowledge, trends and innovations. New platforms are described which combine advances in biomedical sciences, physics, computing and chemistry.